Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11547-013-0319-2
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of noninvasive computed tomography coronary angiography: for a patient-friendly medicine

Abstract: Purpose This study was done to evaluate the psychological state and anxiety of patients undergoing computed tomography coronary angiography (CTCA), and assess their acceptance and satisfaction compared to invasive conventional coronary angiography (CCA). Materials and methods A total of 442 consecutive patients (282 male; mean age 57.7 ± 9.5 years) who underwent CTCA for suspected or known coronary artery disease were evaluated with the Endler Multimodality Anxiety Scales (EMAS) before and after the scan, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…8 9 Indeed, many studies have suggested a high degree of short-term patient satisfaction and preference for CTCA. [10][11][12][13] Here, we have investigated the additional effect of CTCA on the improvements in patients' symptoms following attendance at the rapid access chest pain clinic that included an exercise test in the majority (85%) of attendances. We have made a number of notable and novel observations, some of which may initially seem counterintuitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 9 Indeed, many studies have suggested a high degree of short-term patient satisfaction and preference for CTCA. [10][11][12][13] Here, we have investigated the additional effect of CTCA on the improvements in patients' symptoms following attendance at the rapid access chest pain clinic that included an exercise test in the majority (85%) of attendances. We have made a number of notable and novel observations, some of which may initially seem counterintuitive.…”
Section: Discussionmentioning
confidence: 99%
“…The study design has previously been described 4 and the primary findings published. 12 Participants Participants were recruited from a dedicated cardiology chest pain clinic where they were referred with suspected angina due to coronary heart disease. A total of 4146 patients aged 18-75 were recruited as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, the increase in longevity and the development of new diagnostic and therapeutic strategies lead to a raise in the number of people submitted to diagnostic, screening or follow-up examinations [2]. The direct consequence has been the prevention and the improvement of the outcome of many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety is mainly due to the fear of the uncertainty of procedure, results of the examination, and possible consequence of invasive or not and health impairment [2].…”
Section: Introductionmentioning
confidence: 99%
“…The following step could be to place these results in a prognostic context in comparison with CMR which, in current-day practice, is considered the most accurate tool for infarct characterization in clinical setting. The health technology assessment should be also completed with cost-effectiveness and economic sustainability study (120,121). A one stopshop examination with a profile of first-line imaging could be a solution to cut economic and biological costs in the work-up of patients with suspected or known CAD.…”
Section: Discussionmentioning
confidence: 99%